The Influence of Learning Models and Learning Reliance on Students’ Scientific Literacy (Jurnal Pendidikan IPA Indonesia, 2018)
This research aimed to identify the influence of two learning models and learning reliance on students’ scientific literacy. The method used was the treatment by 2 x 2 level. The participants were 36 students from the Department of Biology Education who were grouped into two categories based on the reliance questionnaire score, i.e., categories of high and low. The data were collected through scientific literacy tests, data analysis using two-path ANOVA formula followed by the Tukey test. The results showed that there was an influence on the interactions between the learning models and learning reliance on students’ scientific literacy seen from the ANOVA test results which obtained F = 29.88, =0.05. The Tukey test analysis identified; (1) Scientific literacy of college students who used the Science, Technology, Society (STS) model was higher than those who adopted the Problem-Based Learning (PBL) Model with Q = 4,74 at =0.05; (2) The scientific literacy of students having high learning reliance using the STS learning model was better than those applying the PBL with Q = 11,78 at =0.05; (3) The scientific literacy of students having low learning reliance using the STS learning model was lower than those using the PBL with Q=5.07 at =0.05. It concluded that the STS learning model could improve the students’ scientific literacy. In other words, the STS learning was more useful for the high reliance students than those with low reliance.